Minutes of the Annual General Meeting 2022. - de Waal, Cornelis (Transactions of the Charles S. Peirce Society)
[as approved on January 5, 2023] The Annual General Meeting of the Charles S. Peirce Society was held virtually via zoom on January 13, 2022. Report from the Nominating Committee and Election of New Officers Ahti-Veikko Pietarinen submitted the following report on behalf of the nominating committee, which Richard Kenneth Atkins read. I (E) Any other business: i Atkins reported that Chiara Ambrosio, in sending her regrets, warmly reminds Peirce scholars are especially welcome to submit panel proposals or individual abstracts for the upcoming European Pragmatism Conference, which she is organizing in London in August. Atkins requested that that amount of money be set aside for funding for scholarship, with which the committee unanimously agreed.